Probabilistic fatigue S-N curves derivation for notched components (Fracture and Structural Integrity, 2017)
Europe has a number of ancient riveted metallic bridges, constructed during the second half of the 19th century up to the middle of the 20th century, which are still in operation. In this paper, a unified approach is presented to generate probabilistic S-N curves to be applied to structural components, accounting for uncertainties in material properties. The approach is particularly demonstrated for a plate with a circular hole, made of puddle iron from the Portuguese Eiffel Bridge. This paper presents an extension of the local strain-based fatigue crack propagation model proposed by Noroozi et al. The latter model is applied to derive the probabilistic fatigue crack propagation field (p-S-Np field). The probabilistic fatigue crack initiation field (p-S-Ni field) is determined using a notch elastoplastic approach, to calculate the fatigue failure of the first elementary material block ahead of the notch root.
Keywords: Fatigue; Probabilistic Approach; Puddle Iron; Notched Plate; Local Approaches